A comparative study on the oxidation state of lattice oxygen among Li1.14Ni0.136Co0.136Mn0.544O2, Li2MnO3, LiNi0.5Co0.2Mn0.3O2 and LiCoO2 for the initial charge–discharge1. Issue 22 (14th June 2015) - Han, Shaojie; Xia, Yonggao; Wei, Zhen; Qiu, Bao; Pan, Lingchao; Gu, Qingwen; Liu, Zhaoping; Guo, Zhiyong
<x xml:space="preserve">Abstract</x> The charge compensation from lattice oxygen in the Li2MnO3 component is responsible for the high specific capacity of Li-rich layered oxides.